Rational or Emotional? An Examination of Customer Loyalty in B2B Packaged Food Retail Setting - Phang Ing @ Grace; Yee, Sheng Sim (2020)
This study aims to examine the contributing rational and emotional transactionspecific characteristics to customer loyalty dimensions, namely repurchase intention and positive words of mouth (WoM); as well as the mediation role of customer satisfaction among the buyers of packaged food retail outlets. A total of 221 responses were collected from the food retail businesses using purposive sampling method. The results demonstrated only four significant contributing factors to customer satisfaction, namely product quality, price perception, brand image and manufacturing country’s product image among the eight factors examined; with product quality and price perception played the most important roles. Proxys of a satisfied customers can be used to predict both behavioural and attitudinal loyalty. The study expands on existing literature by presenting the results of an empirical study addressing the uniqueness of the Malaysian packaged food retail market and how the transaction specific characteristics influence satisfaction and loyalty.